Depletion of endogenous interleukin-10 augments interleukin-1 beta secretion by Mycobacterium bovis BCG-reactive human cells. - Méndez-Samperio, P (1997)
In this study, we found evidence that the interleukin-10 (IL-10) protein is functionally relevant in Mycobacterium bovis BCG-induced cytokine synthesis, as neutralization of endogenously synthesized IL-10 in human cells activated with BCG resulted in a two- to threefold increase in the level of IL-1 beta. When exogenous recombinant human IL-10 was added to human mononuclear cells, a significant reduction of BCG-induced IL-1 beta secretion was observed. This inhibitory effect was not attributed to a cytotoxic effect, since trypan blue exclusion studies indicated no loss of cell viability in the presence of IL-10, and it was specific, as it was completely abolished in the presence of anti-IL-10 neutralizing monoclonal antibody while an irrelevant antibody used as a control had no effect. Taken together, these are the first studies that demonstrate that the depletion of endogenous IL-10 via anti-IL-10 antibody results in a very significantly enhanced BCG-induced IL-1 beta secretion and that the addition of exogenous IL-10 to human mononuclear cells stimulated with BCG inhibits IL-1 beta production. Further experimental work is needed to determine if the neutralization of IL-10 activity via anti-IL-10 antibody indeed enhances cytokine synthesis in vivo. However, the present results may be of importance, since the use of anti-IL-10 antibody could presumably contribute to the protective immunity induced by BCG against tuberculosis via an increase in cytokine synthesis that would amplify antimicrobial systems.